Building trust in long-term care settings using assistive technology: a systematic review - Zheng, Kangjie; Han, Fred; Yang, Siyu; Li, Nanxin (Frontiers in Rehabilitation Sciences, 2024)
BackgroundThis review investigates the dynamics of trust between caregivers and care receivers in long-term care settings, where the implementation of assistive technology also becomes chronically crucial. Trust is essential in the care receiver-caregiver relationship as it impacts the effectiveness of care and the care receiver's participation in treatment. Moreover, integrating assistive technology significantly affects the quality of care by increasing care receivers' autonomy and reducing caregivers' workload. Despite its significance, the mechanisms of trust involving assistive technology in long-term care have not been clarified.MethodsTo address this gap, this review systematically analyzed 32 articles published in English since 2,000, sourced from Web of Science, PubMed, Scopus, and Science Direct databases.ResultsThe review identified the dynamics of trust in long-term care settings involving assistive technology. Based on this trust dynamics, three critical factors were analyzed: care receiver-related, caregiver-related, and assistive technology-related.DiscussionThe findings provide a detailed understanding of the factors affecting trust in long-term care settings involving assistive technology. These insights contribute to long-term care facility operators making informed decisions regarding technology adoption in care practice and care service strategies, ultimately enhancing trust and the quality of care in long-term care settings.